Pengaruh padat penebaran terhadap pertumbuhan ikan lele sangkuriang (Clarias sp) - zainal Berlian; Syarifah Syarifah; Bambang Haryanto (Bioilmi: Jurnal Pendidikan, 2016)
The high costs of maintenance catfish in the pond, making the maintenance of catfish in the narrow land be onealternative maintenance catfish. Among the efforts to increase production of catfish in the maintenance of thenarrow area is to increase stocking density at the pool tarp, and the use of catfish (Clarias sp.) Which issuperior strains, the results of Indonesian researchers. This study was conducted in an investigation on Jl.Slamet Riyadi Lr. Lawang Kidul Darat, Palembang in South Sumatra, in April-May, 2016. The parameters usedare weight, length, and degree of fish life. This research used experimental method completely randomizeddesign (CRD), with 3 treatments, and each 3 repetitions by comparing growth in the control treatment (P0 =100 birds / m2) with treatment P1 (125 individuals / m2), P2 (150 individuals / m2), and P3 (175 individuals /m2). The results showed that there was a significant difference between the treatment given to the growth ofweight, length, and degree of life. P1 treatment gives the best growth of the catfish and significantly different toother treatments (P <0.05). Absolute growth of 8.65 grams, with a length of 5.7 cm.